Comparison of staging systems in gastric carcinoma. Issue 11 (10th August 2021) - Gunduz, Ihsan; Acehan, Turker; Alemdar, Ali; Surel, Aziz Ahmet; Coskun, Nazim
Abstract: Aim: Gastric carcinoma is one of the most frequent cancers and leading causes of cancer‐related death worldwide. Treatment strategies are planned according to the Tumour‐Node‐Metastasis (TNM) stage of the disease. However, the prognosis varies substantially even within the same stage. Prognostic nomograms were designed to overcome this diversity. In this study, staging systems and prognostic tools are compared in the context of their ability to predict patients' prognosis. Methods: Records of 391 patients operated for gastric cancer from January 2006 to September 2013 were analysed retrospectively. TNM staging system, Metastatic lymph node ratio (LNR), Kattan Prognostic Tool and Prognostic Tool of Italian Research Group on Gastric Cancer (GIRCG) were compared with the patients' survival times by their concordance indices and correlation coefficients. Results: A total of 343 patients were included in the study. Concordance indices of the compared staging systems were 0.678 for TNM, 0.601 for GIRCG scale, 0.646 for LNR stage and 0.680 for Kattan scale. Pearson correlation coefficients were 0.404 for TNM staging, 0.314 for GIRCG scale, 0.304 for LNR stage and −0.406 for Kattan scale. Spearman correlation coefficients were 0.383, 0.311, 0.310 and −0.400 respectively. Conclusion: Based on these results, Kattan prognostic scale was found to be the most accurate system for predicting mortality. This was followed by TNM staging system.